“Catastrophization”, Its Weaponization, and Opiophobia: A Perfect Landscape for Unnecessary Harms, or “Catastrophization About Catastrophization”? - Schatman ME; Levin D (Journal of Pain Research, 2024)
Michael E Schatman,1,2 Danielle Levin1 1Department of Anesthesiology, Perioperative Care & Pain Medicine, NYU Grossman School of Medicine, New York, NY, USA; 2Department of Population Health - Division of Medical Ethics, NYU Grossman School of Medicine, New York, NY, USACorrespondence: Michael E Schatman, Department of Anesthesiology, Perioperative Care & Pain Medicine, NYU Grossman School of Medicine, 550 First Avenue, New York, NY, 10016, USA, Tel +1 425-647-4880, Email Michael.Schatman@NYULangone.org